Electronic and Spectral Properties of Polymeric Composites - Kareem, Raqiya Saad Ghaleb; zabaleh, Aya Yassin Kareem; Hussain Abdullah, Fatima Razzaq Abdul; Riyam Ahmed Salman Sajer (American Journal of Botany and Bioengineering, 2024)
The aim of the present work is to present a theoretical study based on the hybrid function of three parameters Lee-Yang-Parr B3LYP of the density functional theory DFT quantum mechanical approach together with the Stuttgart Dresden triple zeta SDD basis sets. All calculations are carried out by employing the used method at the Gaussian 09 package of programs. The studied compounds are three. The electronic structure of the compounds includes the structural, electronic, spectroscopic properties. The results show that the SDD basis sets are efficient strongly suggested for polymers and give good relax for the structures of the studied polymer –dye compounds. The total energy is independent on the position of the dye in the compounds, it depends only on the number of electrons in each compound. From the calculations, the results showed the studied compounds show destabilization of LUMO and stabilization of HOMO, they both changed significantly to suggest different structures play important roles in electronic properties. The effect of symmetry and distribution of dye rings has an influence on the calculation of HOMO and LUMO. In general, most of the studied (PMMA-dye) compounds have electronic transition with wave length lies in the range of ultraviolet spectrum. The compounds in this paper have an application as photovoltaic materials.